Mechanisms of oxygen permeation through plastic films and barrier coatings. (25th September 2017) - Wilski, Stefan; Wipperfürth, Jens; Jaritz, Montgomery; Kirchheim, Dennis; Mitschker, Felix; Awakowicz, Peter; Dahlmann, Rainer; Hopmann, Christian
Abstract: Oxygen and water vapour permeation through plastic films in food packaging or other applications with high demands on permeation are prevented by inorganic barrier films. Most of the permeation occurs through small defects (<3 µ m) in the barrier coating. The defects were visualized by etching with reactive oxygen in a capacitively coupled plasma and subsequent SEM imaging. In this work, defects in SiO x -coatings deposited by plasma-enhanced chemical vapour deposition on polyethylene terephthalate (PET) are investigated and the mass transport through the polymer is simulated in a 3D approach. Calculations of single defects showed that there is no linear correlation between the defect area and the resulting permeability. The influence of adjacent defects in different distances was observed and led to flow reduction functions depending on the defect spacing and defect area. A critical defect spacing where no interaction between defects occurs was found and compared to other findings. According to the superposition principle, the permeability of single defects was added up and compared to experimentally determined oxygen permeation. The results showed the same trend of decreasing permeability with decreasing defect densities.